What Are We Learning? An Update on Abortion Education in Medical Schools [29G]. (May 2020) - Heger, Julie; Roth, Joeli; Kenya, Sonjiya
Abstract : INTRODUCTION: Nearly one in four U.S. women will have an abortion by age 40, making abortion one of the most common medical procedures women undergo in the United States. Despite its prevalence, abortion education has been historically limited in United States (US) medical schools' curricula. The last assessment of medical schools' reproductive health curricula was done in 2005. This research aims to reexamine the status of abortion education. METHODS: We emailed a three-question survey to the Obstetrics & Gynecology clerkship directors at 143 US allopathic medical schools. The survey assessed the availability and type of reproductive health exposure students have during their pre-clinical and clinical years. Participants were invited to complete the survey in April, and reminder emails with the survey link were sent in July and September. RESULTS: Thus far, 79 clerkship directors have responded to the survey, for a response rate of 56%. Ten percent of clerkship directors reported no formal abortion education in preclinical or clinical years. This is compared to 2005, with 17% of clerkship directors indicating no formal abortion education. In the clinical years, 47% of respondents indicated abortion education was integrated into the experience, while 28% reported students had to arrange participation on their own. CONCLUSION: While there has been some increase in the availability of abortion education in U.S. medical schools, this improvement pales in comparison to the national demand for the procedure. As a fundamental aspect of reproductive health, abortion education deserves a place in the curricula at every medical school.